PENERAPAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS PADA MATERI PERUBAHAN SIFAT BENDA - Apriani, Susi; Sudin, Ali; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
Skills Process Sciences (KPS) is a process in doing activities related to science. Scientific process skills can be improved through a lesson that can support students to participate more actively during the learning process. One of the ways used to make students more active during the learning process is by applying contextual teaching or learning (CTL). In learning CTL, teacher's role is as facilitator, motivator, and creator to help construct student's knowledge. CTL learning can improve the science process skills of class V students on material changes in the properties of objects. This is evidenced by the research that has been done by using classroom action research methods that have done for three cycles. Based on the research, the application of CTL can improve the science process skills of Cikondang II State Elementary School students